Ion-molecule reactions catalyzed by a single gold atom. Issue 32 (4th August 2020) - Yang, Shengfu; Wu, Hong; Luo, Qiquan; Al Hindawi, Aula M.; Sitorus, Berlian; Ellis, Andrew M.; Yang, Jinlong
Abstract : Single Au atoms within van der Waals complexes are found to serve as catalysts in ionisation-induced chemistry for the first time. Abstract : We report that Au atoms within van der Waals complexes serve as catalysts for the first time. This was observed in ionization-induced chemistry of 1, 6-hexanediol–Au and 1, 8-octanediol–Au complexes formed in superfluid helium nanodroplets, where the addition of Au atom(s) made C2 H4 + the sole prominent product in dissociative reactions. Density functional theory (DFT) calculations showed that the Au atom significantly strengthens all of the C–C bonds and weakens the C–O bonds in the meantime, making the C–C bonds stronger than the two C–O bonds in the ionized complexes. This leads to a preferential cleavage of the C–O bonds and thus a strong catalytic effect of the Au atoms in the reactions.